The effect of milk processing on protein digestion and amino acid absorption in the gastrointestinal tract of pigs as a model human : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Sciences at Massey University, Manawatū, New Zealand - Ahlborn, Natalie Gisela Marlis (Massey University, 2024)
Globally, milk is processed using heat and homogenisation to improve food safety and extend shelf life. These common processing techniques can alter the native structures present in milk, including protein structures. However, the impact of these processing-induced changes on the digestion of milk protein and subsequent absorption of amino acids in the human body is not yet fully understood. The overall objective of this research was to understand how heat treatment and homogenisation affect milk protein coagulation and digestion in the stomach, and to investigate how changes to gastric coagulation (curd formation) influence amino acid (AA) absorption in the small intestine and AA concentrations in blood circulation. Due to the limited accessibility of the human gastrointestinal tract, pigs were used as a model of the human. An initial study using raw bovine (cow), caprine (goat), and ovine (sheep) milk established the role of gastric curd formation in small intestinal AA absorption in piglets at a single postprandial time point. Specifically, differences in the retention of AA in the gastric curd were responsible for differences in the small intestinal AA absorption across milk of different species. A separate study using bovine milk as a milk model was then conducted to determine the effect of heat treatment and homogenisation on the kinetics of milk protein digestion and small intestinal AA absorption. The selected processing treatments were pasteurisation, ultra-high temperature treatment (UHT), and homogenisation. Raw milk was included as a comparator. In the stomach, heat treatment and homogenisation altered the strength and structure of the curd formed during gastric digestion, which in turn affected both milk protein hydrolysis and the rate of AA entering the small intestine. Differences in the release of digested protein and AA into the small intestine were reflected in the kinetics of AA absorption of the processed milk types. For example, UHT milk had both a faster rate of AA entering the small intestine and a faster rate of AA absorption. Processing also altered the appearance of some AA in blood circulation; however, these differences were not directly reflective of the differences observed in their small intestinal absorption kinetics. In conclusion, this PhD research demonstrated that the rate of small intestinal AA absorption was modulated by gastric curd formation, indicating that milk processing could be used as a strategy to modulate protein digestion and AA absorption in the gastrointestinal tract.
Figures 2.1A, 2.1B, 2.2, 2.3, 2.4, 2.6, 2.7, 2.8 and 2.9 are reproduced with permission.
Chapters 3 and 4 were published under a Creative Commons Attribution 4.0 International (CC BY 4.0) license.
Keywords: Milk proteins; Metabolism; Amino acids; Absorption and adsorption; Homogenized milk; Animal models in research; bovine milk; gastric emptying; protein digestion; amino acid absorption; homogenisation; heat-treatment; in-vivo; 321004 Nutritional science